Evaluation of In-vivo Anti-Depressant, Anti-Anxiety and Anti-Convulsant Activity of Ficus Lacor Bark - Roshan Kumar Mehta; Arjun Saraf; Shankar Thapa; Mukesh Kumar Chaudhary; Vivek Kumar Mehta (Janaki Medical College Journal of Medical Science, 2023)
Background and Objectives: Ficus lacor is a large deciduous, rapidly growing closely foliaceous tree about 20 m in height with a fine shaped crown. It is widely distributed in tropical and subtropical regions of the world. This plant is mentioned in different ayurvedic texts with different therapeutic values and literatures. Ficus lacor is used for its anti-inflammatory, anti-arthritic, antioxidant and anti-diabetic activities from time era. The present study was conducted to evaluate Antidepressant, Anxiolytic and Anticonvulsant activity of Ficus lacor bark using various animal models. Materials and Methods: Wistar rats of either sex weighing 150-250 gram were used in this study. Extract was studied for acute toxicity study. Ethanolic extract of low dose (250 mg/kg) and high dose (500 mg/kg) were performed for anti-depressant, anxiolytic and anti-convulsant activity. Antidepressant and anxiolytic activity were performed by Rota-rod and elevated plus maze. Anti-convulsant activity was studied in isoniazid induced convulsion in Wistar rat. Results: Extract treated 500 mg/kg showed more effective and significant (P<0.05) anti-depressant activity. Extract treated group with 500 mg/kg and 250 mg/kg showed significant anxiolytic activity in both No. of open arm entries and time spent in open arm but have no significant anti- convulsant activity. Conclusion: The study concludes that the ethanolic extract possesses anti-depressant and anxiolytic activity of Ficus lacor bark but have no significant anti-convulsant activity in isoniazid induced convulsion. Our study will aware the community people for the preservation of this medicinal plant and will reduce the wastage of drug by proper utilization of the crude drug.